Rhythmic Gymnastics Training for Cheerful Youth Towards a Fit Indonesia 2045 - Bambang Priyono; Ranu Baskora Aji Putra; Roas Irsyada; Rachmad Irfan Nur; Asyifa Tsalisafriana (QISTINA: Jurnal Multidisiplin Indonesia, 2025)
The characteristics of adolescent students (aged 10–19 years) at the Senior High School (SMA) level demand an effective learning design that supports body health and physical fitness. Creative rhythmic gymnastics accompanied by music is a relevant physical activity proven to reduce stress, improve school performance, and develop students' physical, cognitive, and social qualities. This community service focused on "Cheerful Adolescent Rhythmic Gymnastics Training Towards a Fitter Indonesia 2045 (SRRC)" at SMA Negeri 3 Salatiga. The activity utilized a three-stage training method (Preparation, Implementation, Evaluation) and involved 121 participants. The activity ran smoothly with high enthusiasm, where 80% to 90% of students were able to imitate the SRRC movements which are oriented towards elements of physical fitness (flexibility, balance, coordination, explosive power, and speed). The unique feature of SRRC is the integration of local regional music to foster Nationalism and Bhinneka Tunggal Ika (Unity in Diversity). The movement sequence included a Warm-up, creative Core Movements, and a Cool-down. Overall, the activity provided a significant positive impact on the physical, psychological, and social aspects of adolescent students, contributing to the improvement of adolescents' quality of life and supporting the Fitter Indonesia 2045 vision. It is hoped that similar activities can be continued sustainably.